Mempertahankan Loyalitas Nasabah Melalui Kepuasan Dan Kepercayaan Nasabah - Muslim Muslim; Edi Rahmat Taufik; Lutfi Lutfi (FEB Universitas Sultan Ageng Tirtayasa, 2020)
Today's banking business is ver competitive, it requires hard work by a company to be able to compete with others. For this reason, changes need to be made, including marketing strategy strategies, especially services, because banks are engaged in services. The purpose of this study is to explain the effect of service quality on customer loyalty and customer satisfaction and customer trust as an intervening variable in Serang BPR banks. The research was carried out by taking a sample using 6 x 16 indicators, namely 96 samples at a minimum, but a maximum of 100 respondents were used. Data collection was obtained from 100 respondents, specifically for customers saving savings products at BPR Serang banks. by giving a questionnaire. Processing of respondents' answers was analyzed qualitatively and quantitatively, using analytical engineering methods using Smart PLS version 2.0.m3. The results of the analysis show that the direct influence of service quality on customer satisfaction is positive and significant. and the direct influence of service quality on customer trust is positive and significant. then the quality of service to customer loyalty is positive and non significant. customer satisfaction with customer loyalty is positive and significant. and customer trust in customer loyalty which is positive and significant.